Implementation of Online Learning During the Covid-19 Pandemic Period in Supporting the Physical Distancing Policy at Stikes Rajekwesi Bojonegoro in 2020 - Azizah, Nur; Muhidayati, Wiwik; Luthfia, Erien; Utami, Rina (Universitas Islam Lamongan, 2020)
The Covid-19 pandemic has changed social life, including learning methods. The existence of restrictions on these activities makes higher education institutions carry out online learning. The research objective was to determine the implementation of online learning at the Rajekwesi Bojonegoro station by using a descriptive research design with a sample of students from Stikes Rajekwesi Bojonegoro who were taking online learning taken by using accidental sampling technique totaling 179 respondents. Data obtained by questionnaires distributed online using google form format. And presented as a percentage. The results of research media / online learning applications mostly use the google classroom application, with a total of 175 respondents (97.8%). The most interesting online learning method is discussion forums with a total of 92 respondents (51.4%), online learning is in accordance with the learning needs of students were 165 respondents (92.2%). It was difficult for students to receive learning materials from 151 respondents (84.4%). Obstacles difficult signal with a total of 102 respondents (57%), and do not have facilities at home for online learning, namely 115 respondents (64.5%). The conclusion of the implementation of online learning there are obstacles both from students, lecturers and the system used, especially in this case the network or internet stability and quotas.